A Novel Study: The Effect of Graphene Oxide on the Morphology, Crystal Structure, Optical and Electrical Properties of Lanthanum Ferrite Based Nano Electroceramics Synthesized by Hydrothermal Method - Aydin, Cihat; Aydin, Handan; Taskin, Mustafa; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2019)
Lanthanum Ferrite based nanocomposites were prepared with various Graphene oxide contents by the hydrothermal method. The crystalline structure, morphological properties, electrical and optical properties of samples were investigated. X-ray diffraction results indicate that all the nano electroceramics are polycrystalline with an Orthorhombic structure. Results from scanning and transmission electron microscopes indicate that the Bismuth ferrite/Graphene oxide powders have nanostructure. The optical band gaps of the nano electroceramics were calculated for the various amount of Graphene oxide. The electrical properties of samples were investigated with the temperature depend on conductivity measurements. The measurement shows that the electrical conductivity changes with increasing temperature and graphene oxide dopants of all samples. Activation energy (E-A) values of the nanocomposites decrease with increasing graphene oxide content. The dielectric properties of Lanthanum Ferrite/Graphene Oxide nanocomposites (real and imaginer) with respect to frequency variation (1 KHz-5 MHz) were measured at room temperature. The relative permittivity (epsilon'), dielectric loss (epsilon '') and alternating current conductivity (sigma(ac)) values of the samples were estimated. It is show that (epsilon'), (epsilon '') and (sigma(ac)) increase with increasing frequency. The polarization-electric field hysteresis loop of all Lanthanum Ferrite/Graphene Oxide nano electroceramics was measured at the room temperature. The loop shows proper saturation with enhanced saturation polarization (P-s), remnant polarization (P-r) and coercive electric field (E-c). The obtained findings suggest that the physical and electrical properties of Lanthanum Ferrite/Graphene Oxide nano electroceramics can be changed by Graphene Oxide doping. These materials can be used for a variety of technological applications in the field of dielectric and ferroelectric.
Keywords: Lanthanum Ferrite; Hydrothermal Method; Graphene Oxide; Dielectric Properties; Ferroelectric